Implementasi Model Pembelajaran Project Based Learning Menggunakan Media Flip Chart Untuk Meningkatkan Hasil Belajar Siswa Pada Pelajaran IPS Kelas VII MTS PSM Tanen Rejotangan - Nur Eviani; Nur Isroatul Khusna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Learning models and also media that are less varied in learning can cause students to become bored and get bored quickly, and the lack of precise selection of learning models in conveying material also causes low student learning outcomes, which is the background of this research. This learning uses the Project Based Learning model using Flip Chart media which is carried out at the MTs PSM Tanen Rejotangan school which is considered to be able to improve student learning outcomes. The purpose of this research is to find out the planning, describe the implementation of learning and also the implications of applying the Project Based Learning model using Flip Chart media. This study uses a mixed methods research method. This type of research uses statistical descriptive quantitative and descriptive qualitative. Qualitative data collection techniques used in this study were observation, interviews, and documentation, while quantitative research used data collection with questionnaires. Qualitative data analysis was in the form of data collection, data reduction, data presentation, and drawing conclusions, while quantitative data analysis used the form of single tabulations and percentages. The research results from the implementation of this learning model can improve student learning outcomes in the cognitive, affective and psychomotor aspects of students.